(untitled) (Journal of the Digital Humanities Association of Southern Africa, 2024)
Results showed that 81% of South African children in Grade 4 cannot read for meaning, against an international average of 6%. Reasons for this poor result will be discussed in this paper. One of the resources used in schools in the fight against illiteracy is a school dictionary. There are excellent school dictionaries produced in South Africa, but the two complaints from learners are that there are not enough words, and that the dictionaries are too big and heavy to carry to and from school. Electronic dictionaries have been developed and are available online or from publishers. These offer more presentation space for each entry, more storage space for more entries, as well as more support for learners in the form of colour illustrations, audio, hyperlinks, and other features. However, most South African schools are not equipped to provide electronic dictionaries to learners – either on a central class computer, or on tablets. The devices are too expensive, data is costly and unreliable, and electricity is a problem. The solution that I will present is an updated version of a PED, a personal electronic dictionary, which has the capacity of an electronic dictionary, while being small and light enough for learners to carry to and from school. This device would not need data or electricity to run. The sample entries that I will present will be suitable for a PED and have been specially designed to contain more support for learners learning in their second language.